Training library patrons the ADDIE way - Wegener, D. R. (Debby R.) (Chandos information professional series., 2006)
This book takes an informal and in-depth look at the five steps of the ADDIE model - Analysis, Design, Development, Implementation and Evaluation - as used in library training programmes. With hints and tips and practical advice from other trainers, the aims of the book are to (1) make the training of library patrons a simple task and (2) to show library staff that training can be rewarding and extremely satisfying. Anyone who has had to design a library training programme will know that it can be quite a daunting task without guidelines, but when it comes to the various learning theories and the associated instructional design models, the choice can be overwhelming. This book will help the reader overcome these problems.